‘Mag ik dood van God?’ Enkele gedachten over zelfdoding vanuit christelijk perspectief - Van Holten, Wilko (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Some reflections on suicide from a Christian point of view This article offers some theological reflections on the problem of suicide in the context of a psychiatric disorder. How are we to evaluate this problem from the perspective of faith? It is argued that suicide in such cases can hardly be discussed in moral terms. On the basis of the so called ‘Augustinian eudaemonism’ it is shown that from a Christian point of view the value of human life does not depend on the individuals judgement, but ultimately rests in the love of God. This love provides for the believer the meaning in life in good times and in bad. When the believer can no longer find the meaning of life in God, due to suffering en disease, it is argued that the problem of suicide should be dealt with as a specific version of the problem of evil.